ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DI RESTORAN AYAM PENYAT SURABAYA DI BOYOLALI - Muhammad Danang Saputra (EKOBIS, 2019)
The rate of population growth is so rapid, the needs in the community are also increasing, especially the culinary business. Increased consumer needs, producers are trying to improve the quality of the company. The study was conducted to test the quality of the product, service quality and brand image how it affected the purchase decision of penyet chicken in Surabaya in Boyolali. The study sample used 100 samples. Multiple linear regression analysis method. The results of research on product quality, service quality, and brand image simultaneously have a significant effect on purchasing decisions of penyet surabaya chicken. Product quality, service quality and brand image in a positive and significant effect on purchasing decisions of penyet surabaya chicken. Purchase decision variables can be explained by three independent variables, namely product quality, price, and promotion of 48.0% and the others are influenced by other variables. Keywords: product quality, service quality, brand image, purchase decision